Assessing association of comorbidities with treatment choice and persistence in MS: A real-life multicenter study. (28th November 2017) - Laroni, Alice; Signori, Alessio; Maniscalco, Giorgia T.; Lanzillo, Roberta; Russo, Cinzia Valeria; Binello, Eleonora; Lo Fermo, Salvatore; Repice, Annamaria; Annovazzi, Pietro; Bonavita, Simona; Clerico, Marinella; Baroncini, Damiano; et al.
Abstract : Objective: To assess whether the presence of concomitant diseases at multiple sclerosis (MS) diagnosis is associated with the choice and the treatment persistence in an Italian MS cohort. Methods: We included newly diagnosed patients (2010–2016) followed in 20 MS centers and collected demographic and clinical data. We evaluated baseline factors related to the presence of comorbidities and the association between comorbidities and the clinical course of MS and the time to the first treatment switch. Results: The study cohort included 2, 076 patients. Data on comorbidities were available for 1, 877/2, 076 patients (90.4%). A total of 449/1, 877 (23.9%) patients had at least 1 comorbidity at MS diagnosis. Age at diagnosis (odds ratio 1.05, 95% confidence interval [CI] 1.04–1.06; p < 0.001) was the only baseline factor independently related to the presence of comorbidities. Comorbidities were not significantly associated with the choice of the first disease-modifying treatment, but were significantly associated with higher risk to switch from the first treatment due to intolerance (hazard ratio 1.42, CI 1.07–1.87; p = 0.014). Association of comorbidities with risk of switching for intolerance was significantly heterogeneous among treatments (interferon β, glatiramer acetate, natalizumab, or fingolimod; interaction test, p = 0.04). Conclusions: Comorbidities at diagnosis should be taken into account at the first treatment choice because they are associated with lower persistence on treatment.